Strengthening Spirituality And Social Concern Through The Huwal Habib Dhikr Routine With A Former Gang Member Community In Keputih Sub-District, Sukolilo, Surabaya - Muhammad Nasrul Waton; Fathoni; Ahmad Futuhal Arifin; Akhmad Suhartono; Mohammad Ahyanul Wafi; Maulana Achmad Kurniawan; Mohammad Su’udun Nafis (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
ABSTRACT This study aims to examine the role of a dhikr group in strengthening spiritual aspects and fostering social care among former thugs in Keputih Village, Sukolilo, Surabaya. Using a qualitative approach with a case study method, this research finds that the practice of Huwal Habib group dhikr, led by a local religious figure, is capable of shaping spiritual awareness and social solidarity among individuals with troubled pasts. The dhikr serves as a means of introspection, heart purification, and drawing closer to Allah SWT. On the other hand, this activity also gives rise to tangible social care in the form of community service, assistance to others, and community development activities. The results of this study demonstrate that a collectively implemented spiritual approach can reconstruct social identity and form an inclusive and transformative community.